The influence of task‐ and location‐specific complexity on the control and coordination costs in global outsourcing relationships - Handley, Sean M.; Benton, W.C. (Journal of Operations Management, 2013)
AbstractSeveral reputable industry sources have recognized that many organizations fail to realize the financial benefits sought with outsourcing. Further, prior research has found that outsourcing organizations struggle to estimate accurately the so called “hidden costs” associated with managing these inter‐organizational relationships. This is especially true of complex, globally distributed outsourced services. In this study, we use dyadic data on 102 outsourcing relationships to investigate how dimensions of task‐ and location‐specific complexity influence the degree of control and coordination costs incurred by the customer organization. Results from our hierarchical regression analysis demonstrate that the scale of the service and the geographic distance between the customer and provider locations are associated with higher levels of both control and coordination costs. Task breadth and geographic dispersion are significantly associated with increased control costs, but not coordination costs. Counter to our expectations, control costs decrease with the degree of service customization, whereas both control and coordination costs are negatively related to the average cultural distance between provider and customer organizations. These findings contribute unique empirical evidence to the outsourcing, offshoring, and international service operations literature.